(untitled) (Research, Society and Development, 2022)
Coccidioidomycosis is a deep mycosis caused by dimorphic fungi of the genus Coccidioides. Clinical manifestations of Coccidioides spp. infection can be considerably diverse. The main clinical form of coccidioidomycosis is respiratory infection which most frequent signs and symptoms are cough, dyspnea, chest pain, fever, arthralgia, myalgia, fatigue, and weight loss. Pulmonary coccidioidomycosis, especially acute pneumonia, can be easily confused with other pneumopathies, including COVID-19. The aim of this manuscript is to perform a systematic review coccidioidomycosis cases in patients with SARS-CoV-2 infection or individuals who developed this mycosis in the period after COVID-19. The context of COVID-19 and its treatment with corticosteroids cn ease the infection with Coccidioides spp. or reactivation of latent infections of this fungus. The main life risk for those affected by coccidioidomycosis concurrent or subsequent to COVID-19 is late diagnosis. The use of corticosteroids in the treatment of COVID-19 and diabetes are the most relevant risk factors for the development of infection with Coccidioides spp. or the reactivation of latent fungal infection. Laboratory biopsy and culture tests of patient’s airways and skin lesions, as well as serology to diagnose coccidioidomycosis, should be incorporated into the routine evaluation of secondary infections in COVID-19 and pneumopathies subsequent to SARS-CoV-2 infection, mainly among more susceptible individuals in regions of high endemicity.